PENDIDIKAN KARAKTER PERSPEKTIF HADITS - Jannah, Sitti Riadil (Jurnal Pendidikan Kreatif, 2023)
Basically, education is not just a process of transferring knowledge in the cognitive dimension from educators to students but much deeper than that education must be able to empower students in other dimensions, namely the psychomotor dimension or affective dimension. The concept of character education (affective dimension) of interest to be developed of how the concept of character education in the perspective of the hadith and its relevance to the concept of character education in the contemporary era with reference to the hadith of the concept of character education when the fetus is still in the womb and the concept of character education in the stages of child development after birth. Hadith's understanding of the concept of character education, when the fetus is still in the womb, showed the provisions of Allah. the child while still in the womb of his mother who in this case is sex, death, and sustenance indicates that the child already has the potential to receive influence from the outside so that children who are still in the womb of need to continue to be treated with the values ​​of character education through various way to keep emotions in order to remain stable mom, eat kosher food, listen to the recitation of the Koran or the moral worth of music, and the like. Understanding the hadith about the concept of character education in the stages of child development after birth showed that the phases of the order of prayer in children begin with the command at age 7 years ago with a punch at the age of 10 years if they do not want to do give clues about the stages of character education, time, and objects formal and material that needs to be applied in accordance with the concept of education for the contemporary era.